Brunei dalam sejarah China - Wu, Zong Yu 1939- (Bandar Seri Begawan Pusat Sejarah Brunei, Kementerian Kebudayaan, Belia dan Sukan, 2010)
History of Brunei Darusalam in Chinese manuscript records.
Parallel title on cover in Chinese characters.
Includes bibliographical references (pages [433]-435).
Manuscript in Chinese and translated to Malay.
AC-14545d donated by Roderick G. Orlina
Keywords: Manuscripts, Chinese; Brunei -- History